Warming enhances the stimulatory effect of algal exudates on dissolved organic carbon decomposition. (25th August 2019) - Wyatt, Kevin H.; Rober, Allison R.
Abstract: The current paradigm in peatland ecology is that the organic matter inputs from plant photosynthesis (e.g. moss litter) exceed that of decomposition, tipping the metabolic balance in favour of carbon (C) storage. Here, we investigated an alternative hypothesis, whereby exudates released by microalgae can actually accelerate C losses from the surface waters of northern peatlands by stimulating dissolved organic C (DOC) decomposition in a warmer environment expected with climate change. To test this hypothesis, we evaluated the biodegradability of fen DOC in a factorial design with and without algal DOC in both ambient (15°C) and elevated (20°C) water temperatures during a laboratory bioassay. When DOC sources were evaluated separately, decomposition rates were higher in treatments with algal DOC only than with fen DOC only, indicating that the quality of the organic matter influenced degradability. A mixture of substrates (½ algal DOC + ½ fen DOC) exceeded the expected level of biodegradation (i.e. the average of the individual substrate responses) by as much as 10%, and the magnitude of this effect increased to more than 15% with warming. Specific ultraviolet absorbance at 254 nm (SUVA254 ), a proxy for aromatic content, was also significantly higher (i.e. more humic) in the mixture treatment than expected from SUVA254 values in single substrate treatments. Accelerated decomposition in the presence of algal DOC was coupled with an increase in bacterial biomass, demonstrating that enhanced metabolism was associated with a more abundant microbial community. These results present an alternative energy pathway for heterotrophic consumers to breakdown organic matter in northern peatlands. Since decomposition in northern peatlands is often limited by the availability of labile organic matter, this mechanism could become increasingly important as a pathway for decomposition in the surface waters of northern peatlands where algae are expected to be more abundant in conditions associated with ongoing climate change.